Redefining Indonesia “Bela Negara” in the Context of Digital Era: Deeper Meaning on National Security Concept - Amaritasari, Indah Pengastu (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2025)
This paper explores how the concept of Bela Negara (state defense) in Indonesia must be redefined in light of evolving global security dynamics, especially amid digital transformation and the rise of hybrid threats (HT) and hybrid warfare (HW). Through a normative juridical and comparative approach, the study examines legal frameworks in Indonesia and other countries such as Singapore, Sweden, and the United States, highlighting differences in how citizen participation, resilience, and national security are framed. It argues that Bela Negara in Indonesia remains heavily tied to a traditional, militaristic understanding of security and must shift toward a more holistic model rooted in national resilience. Such a model includes individual, community, and institutional capacities to resist digital disinformation, violent extremism, and hybrid campaigns. Drawing lessons from total defense models and international frameworks on human rights and security, the article suggests aligning Bela Negara with democratic values, critical digital literacy, and a whole-of-society approach. This reconceptualization is necessary to ensure that Indonesian national security frameworks remain adaptive and inclusive in facing both conventional and emerging threats.